Project design and technology trade-offs for implementing a large-scale sexual and reproductive health mHealth intervention: Lessons from Sierra Leone - Chukwu, Emeka; Gilroy, Sonia; Dickson, Kim Eva (Frontiers in Digital Health, 2023)
Background: The Coronavirus 2019 pandemic threatened decades of progress in Sexual Reproductive Health (SRH) and gender-based violence (GBV) as health facility attendance plummeted and service uptake dwindled. Similarly, COVID-19 misinformation was rife. The demographics in Sierra Leone are diverse in education, economic, and rural/urban divide. Telecommunications coverage, phone ownership, and preference for information access medium also vary greatly in Sierra Leone. Aim: The intervention aims to reach Sierra Leonians at scale with SRH information during a major pandemic. This paper presents the approach and insights from designing and implementing a largescale mobile health messaging campaign. Method: Between April and July 2020, a cross-sectional multi-channel SRH messaging campaign was designed and launched in Sierra Leone. Through a secondary analysis of project implementation documents and process evaluation of the messaging campaign report the project design trade-offs and contextual factors for success were identified. Result: A total of 1.16 million recorded calls were initiated, 35.46 million text messages (SMS) were sent to telecommunication subscribers through a 2-phased campaign. In phase one, only 31% of the 1,093,606 automated calls to 290,000 subscribers were picked up, dropping significantly at 95% confidence (p=1) after each of the four weeks. Also, the listening duration dropped by a third when a message was repeated compared to the first three weeks. Lessons from phase one were used to design an SMS and radio campaign in the scale-up phase. Evidence from our analysis suggest that successful scaling of mHealth interventions during a pandemic will benefit from formative research and depend on at least six factors, among others: i) the delivery channels’ selection strategy, ii) content development and scheduling, iii) the persona categorization of youths, iv) stakeholder collaboration strategies, v) technology trade-offs, and vi) cost considerations. Discussion and Conclusion: The design and implementation of a large-scale messaging campaign is a complex endeavor that requires research, collaboration with diverse other stakeholders, and careful planning. Key success ingredients are essential in the number of messages to be delivered, the format, cost-consideration, and whether or not engagement is necessary. Lessons for similar low-and-middle-income countries are discussed.